Design and Finance of Al-Husna School Canten Web Design Using Prototype Method - Muhammad Subhana (bit-Tech, 2024)
Designing a simple financial system that will be used by Al-Husna School canteen members to deposit how much food goes into the canteen and how much profit the food sold requires a prototype method in building Web Design for an initial overview when a simple financial system is created. used. The problem that occurred in this research was that the financial balance sheet for canteen income and expenditure was not effective, resulting in data not being recorded accurately and not being transparent between members of the Al-Husna canteen, so that after the system was created via Web Design as a prototype, it was also included in the assessment for further research. strong use of the Variable User Centered Design Indicator with a Likert scale formula to add up and produce an understanding of the position of Canteen Member Users with information according to the predetermined weight values. This Web Design uses HTML, CSS and Java Script languages in its used. The results of this research were assessed by 10 canteen member respondents that the Al-Husna Canteen Financial Web Design indicator value for Learnability was 83, Efficiency was 84, Satisfaction was 86, Error Prevention was 86, and Memorability was 84, the average value was 84.6 which This means that the appearance of Al-Husna Canteen Financial Web Design is attractive in terms of use and display content.